2014
DOI: 10.15326/jcopdf.1.1.2014.0120
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Genetics: A Review of the Past and a Look Into the Future

Abstract: Abbreviations: single nucleotide polymorphism, SNP; genome-wide association studies, GWAS; forced expiratory volume in 1 second, FEV1; early-onset COPD, EOCOPD; National Emphysema Treatment Trial, NETT; Normative Aging Study, NAS; International COPD Genetics Network, ICGN; linkage disequilibrium, LD; Evaluation of COPD Longitudinally to Identify Surrogate Endpoints, ECLIPSE; cigarettes per day, CPD; forced volume capacity, FVC; Cohorts for Heart and Aging Research in Genetic Epidemiology Consortium, CHARGE; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 65 publications
0
31
0
1
Order By: Relevance
“…Several studies have demonstrated the role of genetic factors in COPD development [179,180], with naturally occurring mutant murine models [165,181], conditional transgenic [182,183], and transgenic animals [184][185][186] developing emphysema. Murine models are favored over other animal models due to their large litter size and fast reproductive cycle, which speeds up the selection of favorable genetic traits that can be used in disease models [187].…”
Section: Genetic Manipulationmentioning
confidence: 99%
“…Several studies have demonstrated the role of genetic factors in COPD development [179,180], with naturally occurring mutant murine models [165,181], conditional transgenic [182,183], and transgenic animals [184][185][186] developing emphysema. Murine models are favored over other animal models due to their large litter size and fast reproductive cycle, which speeds up the selection of favorable genetic traits that can be used in disease models [187].…”
Section: Genetic Manipulationmentioning
confidence: 99%
“…After the trials and tribulations of the candidate gene era in COPD genetics, the arrival of GWAS provided a welcome source of more consistent genetic association results for COPD (11). As noted above, to overcome the multiple statistical testing adjustments in GWAS, stringent levels of statistical significance (typically…”
Section: Progress In Chronic Obstructive Pulmonary Disease Genetics Amentioning
confidence: 99%
“…Many of these suffered from limited coverage of the genetic variation in target genes and small sample sizes thus limiting interpretation due to the lack of replication. These studies have been reviewed in detail elsewhere (Hardin M, 2014). Of note, a well powered study (8,300+ subjects) using a candidate gene approach identified association between SNPs in the matrix metalloprotease 12 gene (MMP12) and both FEV1 and COPD risk (Hunninghake et al, 2009).…”
Section: Genetic Mapping Of Lung Function Genes: Linkage Analysesmentioning
confidence: 99%